EFL LEARNERS’ LEARNING STYLE PREFERENCES IN RELATION TO THEIR ENGLISH PROFICIENCY - Manan, Siti Saleha; Suhartini, Lelly; Muhsin, Muhammad Khusnun (Journal of Teaching of English, 2019)
The aim of this study was to find out students’ learning style preference and its correlation with their English Proficiency. The research questions were as follows (1) what are the most preferred learning styles of EFL Learner at English Department? (2) Is there any significant correlation between students’ learning style preferences and their English Proficiency? The study used Correlation design. The number of sample in this study was 35 students from English department of Halu Oleo University in the academic year who had followed TOEFL test. The data were collected using questionnaire which adopted   Perceptual   Learning-Style   Preference   Questionnaire   (PLSPQ), developed by John Reid (1987) consisting of 30 statements and student’s TOEFL  score.  The  data  of  this  study  were  analyzed  through  descriptive statistic and Linear Regression Analysis. The results showed that (1) major learning style were tactile learning style and kinesthetic learning style (2) The coefficient correlation was 0.070 which was greater than 0.05 (level of significance).  It  means  that  there  was  no  correlation  between  students’ learning style and their English proficiency.Keywords: Student’s Learning Style, English Proficiency.